Dicarabrol A, dicarabrone C and dipulchellin A, unique sesquiterpene lactone dimers from Carpesium abrotanoides. Issue 8 (16th January 2017) - Wu, Jie-Wei; Tang, Chunping; Ke, Chang-Qiang; Yao, Sheng; Liu, Hong-Chun; Lin, Li-Gen; Ye, Yang
Abstract : Three sesquiterpene lactone dimers with an unprecedented skeleton were isolated from the whole plants of Carpesium abrotanoides . Abstract : Three rare sesquiterpene lactone dimers, dicarabrol A (1 ), dicarabrone C (2 ) and dipulchellin A (3 ), were isolated from the whole plants of Carpesium abrotanoides . Their structures were elucidated by comprehensive analyses of NMR and MS spectroscopic data. The structure of dipulchellin A was further confirmed by single-crystal X-ray crystallography. Compounds1 and2 possessed an unusual carbon skeleton with two carabranolide moieties linking through a spirotetrahydrofuran ring, which was presumably formed by a [4 + 2] cycloaddition. Compound3 was a [3 + 2] cycloaddition product of a guaianolide moiety and a carabranolide moiety linking through a cyclopentane ring. Their plausible biosynthetic pathways were also proposed. Compounds1–3 showed moderate cytotoxicity against HL-60 cells with IC50 values of 8.7 ± 0.3, 8.2 ± 0.3 and 8.9 ± 0.4 μM, respectively.